Juan José Nieto Gil, artistic practices and the genealogy of coloniality in Colombia. Issue 2 (3rd April 2023) - Ariza Aguilar, Ada Margarita
ABSTRACT: As an artistic intervention, the exhibit ¿Suficientemente Negro? ( Black Enough? ) critically examines 'whiteness' and 'racialization' in Colombia. With the purpose of analyzing their impact on the figure of President Juan José Nieto Gil (1804–1866), this exhibit and consequently this article reveal the colonial cultural constructions that worked to whiten, conceal, and erase his image and legacy from Colombia's official history because of his ethno-racial, social, and geographic origins. The artistic approach adopted proved relevant to better understand the weight of the colonial matrix of power in the present and across the various aspects of daily life. I uncover the relationship between race and nation in Colombia as constructed by the Creole elites and intellectuals around the turn of the 20 th century. I center the history of the presidential portrait of Nieto Gil within Colombia's racial hierarchy and the ideas around whiteness that characterize the colonial period. As racial ideas remain steadfast in the biographical and genealogical trajectories of many families in Colombia, I show how Nieto Gil's legacy and erasure overlaps with my own family's history. I describe a collaborative artistic project that interrogates the social constructions of whiteness.